RESEARCH AND IMPACT OF MATERIALS SCIENCE PUBLICATIONS IN INDIA: 1999-2008 - B. S., Kademani; Anil, Sagar; K., Bhanumurthy (Malaysian Journal of Library and Information Science, 2017)
The study analyses the materials science publications in India for a period of ten years (1999-2008) based on the Scopus database. The objective of the study was to perform a scientometric analysis of all materials science research publications by Indian scientists. The parameters studied include growth of publications and citations, relative growth rate and doubling time, domain-wise distribution of publications and citations, activity index, Citation Index, national and international collaboration, highly productive institutions, highly productive authors, highly preferred journals and highly cited publications. A total of 14849 publications were published by the Indian scientists in materials science during 1999-2008 which received 94610 citations. The average number of publications per year was 1484.90. The average number of citations per publication was 6.37. The highest number of publications 1953 was published in 2007. The highest number of citations 12901 was received in 2003. There were 11961 (80.55%) national collaborative publications and 2190 (14.75%) international collaborative publications by the scientists from India with 59 countries. Indian Institute of Technology-Kharagpur topped the list with 1243 publications which received 7985 citations, followed by Indian Institute of Science-Bengaluru with 1052 publications and 8816 citations, and Bhabha Atomic Research Centre-Mumbai with 818 publications and 4252 citations.